A tunable dual-band graphene-based perfect absorber in the optical communication band. (December 2018) - Yue, Jing; Luo, Xin; Zhai, Xiang; Wang, Lingling; Lin, Qi
Highlights: Dual-band perfect absorption peaks are realized in the optical communication regime. By changing the lateral displacement of the two different holes, multiple absorption peaks could also be achieved. The wavelengths of absorption peaks could be shifted, while the values of absorption peaks are almost unchanged. Our proposed absorber also demonstrates polarization-dependence. Abstract: In order to remarkably enhance its absorption capability, a tunable dual-band graphene-based perfect absorber is proposed. By using the finite-difference time-domain (FDTD) simulations, dual-band perfect absorption peaks are realized in the optical communication regime based on the critical coupling effect. By changing the lateral displacement of the two different holes, multiple absorption peaks could also be achieved. Furthermore, by manipulating the widths of air trenches, the wavelengths of absorption peaks could be shifted, while the values of absorption peaks are almost unchanged. Moreover, our proposed absorber also demonstrates polarization-dependence.